DESAIN DAN SIMULASI PENGATURAN SUHU VENDING MACHINE MAKANAN MENGGUNAKAN ADAPTIVE NEURO FUZZY INFERENCE SYSTEM(ANFIS) - muhammad fauqi asyrafi; Moh. Zaenal Effendi; Endro Wahjono (Jurnal Teknologi Terpadu, 2023)
The current temperature control system has developed rapidly and has been used in various fields, one of which is the food industry. As we know in the presentation of food, temperature is a very influential thing in the taste of the food. With the development of technology, the way humans sell is now more modern, one of which is selling with vending machines. It is very important to pay attention to the selection of the method in setting the right vending machine temperature to avoid reduced enjoyment in consuming the products sold due to changes in the temperature that has been determined. Therefore, in this study, the Anfis method is proposed for temperature regulation in vending machines. From the simulation results from the simulation results, the Anfis control can accelerate the temperature in reaching the set point and can also maintain the temperature to the set point